The sweetest thing: blocking fructose metabolism to prevent acute kidney injury? - Wyatt, Christina M. (Kidney Int, 2017)
Fructose consumption has been linked to hypertension in animal models and human studies, and endogenous fructose metabolism has been shown to promote acute and chronic kidney injury in mice. A recent study published in Nature Communications demonstrates a reduction in ischemic acute kidney injury with genetic knockout or inhibition of fructokinase, which catalyzes the first step in fructose metabolism. Although the role of this pathway in human kidney disease remains unclear, the recent description of several candidate fructokinase inhibitors may allow for clinical studies in the future.